Surface plasmon resonance: principles, methods and applications in biomedical sciences. Issue 2 (2003) - Englebienne Englebienne, Patrick Patrick; Hoonacker Hoonacker, Anne Van Anne Van; Verhas Verhas, Michel Michel
Abstract : Surface plasmon resonance (SPR) is a phenomenon occuring at metal surfaces (typically gold and silver) when an incident light beam strikes the surface at a particular angle. Depending on the thickness of a molecular layer at the metal surface, the SPR phenomenon results in a graded reduction in intensity of the reflected light. Biomedical applications take advantage of the exquisite sensitivity of SPR to the refractive index of the medium next to the metal surface, which makes it possible to measure accurately the adsorption of molecules on the metal surface and their eventual interactions with specific ligands. The last ten years have seen a tremendous development of SPR use in biomedical applications. The technique is applied not only to the measurement in real-time of the kinetics of ligand–receptor interactions and to the screening of lead compounds in the pharmaceutical industry, but also to the measurement of DNA hybridization, enzyme–substrate interactions, in polyclonal antibody characterization, epitope mapping, protein conformation studies and label-free immunoassays. Conventional SPR is applied in specialized biosensing instruments. These instruments use expensive sensor chips of limited reuse capacity and require complex chemistry for ligand or protein immobilization. Our laboratory has successfully applied SPR with colloidal gold particles in buffered solution. This application offers many advantages over conventional SPR. The support is cheap, easily synthesized, and can be coated with various proteins or protein–ligand complexes by charge adsorption. With colloidal gold, the SPR phenomenon can be monitored in any UV-vis spectrophotometer. For high‒throughput applications, we have adapted the technology in an automated clinical chemistry analyzer. This simple technology finds application in label-free quantitative immunoassay techniques for proteins and small analytes, in conformational studies with proteins as well as in the real-time association-dissociation measurements of receptor–ligand interactions, for high-throughput screening and lead optimization.